Fallibility at Work Rethinking Excellence and Error in Organizations - Kvalnes, Øyvind (Springer Nature, 2017)
This book is published open access under a CC BY 4.0 license. This book addresses how organizations can deal with human fallibility in order to create space for excellence at work. Some mistakes in work settings put lives at risk, while others create openings for innovative breakthroughs. In order to deal constructively with fallibility, an organization needs a communication climate where it is normal to voice opinions, admit mistakes, and ask for help in critical situations. The book builds on interviews with practitioners in healthcare, aviation, IT, public governance, and industry. It connects narratives from these fields with theories from organizational psychology and philosophy, as well as from positive organizational scholarship. In the final chapter, an overall ethics of fallibility at work is outlined. Fallibility at Work contributes to research in multiple academic disciplines, but also reaches out to practitioners who are interested in the connections between error and excellence in organizations. ; Provides a systematic account of what the phenomenon of fallibility amounts to, why it matters, why it turns out to be difficult to cope with, and finally how we may deal with it in constructive ways Highlights the relational aspects of organizational behaviour, with theoretical input from the three disciplines of philosophy, psychology and pedagogy Explores how the challenges posed by fallibility change when emphasis moves from heroic to distributed leadership, and from vertical to horizontal leadership Open Access